Attosecond transient absorption spooktroscopy: a ghost imaging approach to ultrafast absorption spectroscopy. Issue 5 (3rd December 2019) - Driver, Taran; Li, Siqi; Champenois, Elio G.; Duris, Joseph; Ratner, Daniel; Lane, Thomas J.; Rosenberger, Philipp; Al-Haddad, Andre; Averbukh, Vitali; Barnard, Toby; Berrah, Nora; Bostedt, Christoph; et al.
Abstract : Recently demonstrated isolated attosecond XFEL pulses should allow the probing of ultrafast electron dynamics at X-ray wavelengths. The authors use ghost imaging to enable high-resolution transient absorption spectroscopy at fluctuating XFEL sources. Abstract : The recent demonstration of isolated attosecond pulses from an X-ray free-electron laser (XFEL) opens the possibility for probing ultrafast electron dynamics at X-ray wavelengths. An established experimental method for probing ultrafast dynamics is X-ray transient absorption spectroscopy, where the X-ray absorption spectrum is measured by scanning the central photon energy and recording the resultant photoproducts. The spectral bandwidth inherent to attosecond pulses is wide compared to the resonant features typically probed, which generally precludes the application of this technique in the attosecond regime. In this paper we propose and demonstrate a new technique to conduct transient absorption spectroscopy with broad bandwidth attosecond pulses with the aid of ghost imaging, recovering sub-bandwidth resolution in photoproduct-based absorption measurements.